PERADABAN MELAYU SARAWAK DALAM KONTEKS NUSANTARA - Mansor, Suffian; Awang Pawi, Awang Azman (JURNAL MELAYU SEDUNIA, 2019)
The objective of this study was to analyze the concept of civilization and the influence of the old polity and Islamic civilization to the development of the Sarawak Malay civilization. The effect of civilization is a boost to the Sarawak Malay civilization will be analyzed using an analytical approach from the historical perspective. Based on this study, the influence of the Majapahit polity, Brunei and Islamic civilization has a very strong impact on the socio-cultural, political, economic and religious aspects of Islam. These include the results of historical, social, cultural and administrative systems. But the effect of the presence of Brooke and administration has given the impact on the Malay culture including traditional Malay political dominance eliminated and has been replaced by the western-style system, a threat to Islam, but reinforce efforts to strengthen aspects of ethnicity and Islam. As a result, Brooke era also caused the golden age of Malays as a trader and Nakhoda slipping and experiencing a severe downturn. This is further compounded by the influx of foreign migrants to Sarawak. On a more positive aspect, modern education to Malay children and led to the emergence of a generation of Malay intellectuals that were aware of the problems of their society. Sarawak Malay civilization is also hampered by the Japanese and the British. Sarawak’s participation in Malaysia helps to restore some of the Sarawak Malay civilization but the effects of colonialism still remain.